Anticancer Effects of Novel Tetrahydro-Dimethyl-Xanthene-Diones - Manikandan, Alagumuthu; Sivakumar, Arumugam; Nigam, Poonam S.; Napoleon, Ayyakannu A. (Anti-Cancer Agents in Medicinal Chemistry, 2020)
Background: The derivatives of xanthene are known to have promising anticancer properties, in comparison to xanthene itself. Objective: The object of our study was to develop few xanthene derivatives (a family of fifteen novel 3,4,6,7- tetrahydro-3,3-dimethyl-9-phenyl-2H-xanthene-1,8(5H, 9H)-diones encoded as 4a-4m), which were effectively prepared through regioselective synthesis approach, and to test their anticancer effects. Methods: A series of cell lines were used in this study, first to assess the cytotoxicity and then the drug efficacy of target compounds, consecutively. Prior to MTT assay, the compounds were analysed for their antioxidant properties, since oxidative stress is an important factor in the development of many cancer types. The anticancer properties of 4a-m have been assessed over in silico (molecular docking and ADMET assessments) and in vitro (MTT assay) methods. Results: Compounds 4h and 4i showed a relative percentage anticancer activity of 86.25±1.25 & 89.74±1.64 against BT474 (ER+HER2+), and 90.56±1.18 & 93.24±1.80 against MCF-7 (ER-HER2), respectively. Conclusion: The animal model and pre-clinical studies for 4h and 4i should be performed in order to develop them as future anticancer agents.
Keywords: Anticancer